2012
DOI: 10.2310/jim.0b013e31824963b6
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of PAI-RBP1, C1orf142, and COTL1 in Non–Small Cell Lung Cancer Cell Lines with Different Tumor Metastatic Potential

Abstract: Human non-small cell lung cancer (NSCLC) is one of the most common malignancies in the modern world. Its recurrence is mainly due to its ability to invade and metastasize. However, the precise mechanism for tumor development and metastasis is still not fully understood. To shed light on the development of lung cancer, the human giant cell lung carcinoma cell lines 95D with high metastatic potential and 95C with low metastatic potential were selected in this study. The 2 cell lines originated from the same pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…1A), the phenotype differences between the two cell lines are consistent with those reported previously (29,30). Thus, we examined the expression of DCN mRNA in low-(95C) and high-metastatic (95D) human NSCLC cell lines using qRT-PCR analysis, and found that DCN mRNA expression in 95D cells was lower by far than that in 95C cells (P<0.01) (Fig.…”
Section: Dna Methylation Is Involved In Dcn Mrna Expressionsupporting
confidence: 89%
See 2 more Smart Citations
“…1A), the phenotype differences between the two cell lines are consistent with those reported previously (29,30). Thus, we examined the expression of DCN mRNA in low-(95C) and high-metastatic (95D) human NSCLC cell lines using qRT-PCR analysis, and found that DCN mRNA expression in 95D cells was lower by far than that in 95C cells (P<0.01) (Fig.…”
Section: Dna Methylation Is Involved In Dcn Mrna Expressionsupporting
confidence: 89%
“…Decreased expression of DCN was found to be significantly associated with lymphatic metastasis of lung cancer patients (23). In the present study, we focused on low-(95C) and high-metastatic (95D) NSCLC cells, which were more genetically similar to each other and could be an ideal model for cancer metastasis (29,30), and found that DCN mRNA was significantly lower in 95D cells compared with that in 95C cells, supporting the idea that DCN was involved in metastasis of malignant tumors, including lung cancer. Additionally, demethylating drug 5-Aza restored DCN mRNA expression in 95D cells, suggesting the involvement of DNA methylation in DCN expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently coactosin expression levels have been associated with the metastatic potential of lung cancer cell lines [135]. In our samples it showed an average expression level of 13.6x with respect to the nontumoral tissues.…”
Section: Coactosin Cotl1 (Cotl1)mentioning
confidence: 53%
“…95C and 95D cell lines share a similar genetic background [29][30]. 5-aza-2 -deoxycitidine (5-Aza) (Sigma-Aldrich, St. Louis, MO, USA) was used as demethylating agent to treat cells.…”
Section: Cell Culture and Drug Treatmentmentioning
confidence: 99%